Interpreting and children in refugee transit zones: The Greek case - (:unkn) unknown (My University, 2024)
Interpreters play a pivotal role in facilitating communication within refugee transit zones, where access to essential services relies on accurate interpretation. In Greece, a key entry point for refugees into Europe, interpreters face numerous challenges, including inadequate training, emotional and cultural complexities, as well as logistical constraints, mainly when working with vulnerable populations. This thesis delves into these communication barriers, focusing on child refugees. Based on qualitative interviews with NGO representatives, a government consultant, and an interpreter, alongside a literature review, the study highlights the need for enhanced training and support systems, identifying critical areas for improvement. Finally, the analysis of the present paper sheds light on the mediating role of interpreters in safeguarding child refugees' rights, urging policy reforms at multiple levels to better address their needs and ensure their protection in transit zones.
Keywords: Interpreting in humanitarian contexts, child refugees, child brokering, refugee transit zones, cultural mediation, emotional resilience, interpreter training, policy reforms